KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 31 PADANG - Khairiah, Citra Yaumil; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is to describe the following matters. First, it describes the reading skills of students in class VII of SMP Negeri 31 Padang. Secondly, it describes the writing skills of the description text of grade VII students of SMP Negeri 31 Padang. Third, explaining the relationship between reading comprehension skills and description writing skills for grade VII students of SMP Negeri 31 Padang. The population of this research is VII grade students of SMP Negeri 31 Padang who are enrolled in the 2018/2019 school year with 256 students spread in eight classes. The sample in this study amounted to 48 people. Samples were taken using a simple random technique with a proportion of 20% using a proportional random sampling technique. Based on the results of the study, the following three things were concluded. First, the reading skills of Grade VII students of SMP Negeri 31 Padang meet good qualifications. This is calculated based on an average count of 81.80. Second, the writing skills of the description text of grade VII students of SMP Negeri 31 Padang in accordance with qualifications is more than enough. This can be seen from the average description text written test of 79.51. Third, a significant discussion between reading comprehension skills and description writing skills of Grade VII students of SMP Negeri 31 Padang at n-1 degrees of freedom and a significant level of 95%. H0 is rejected and H1 is accepted because the results prove the value of tcount is greater than t table 8.01> 1.68.Â Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman, Keterampilan Menulis Teks Deskripsi